Effects of Simulated Solar Wind on Polymethyl Methacrylate Thin Film - Lidia Mezzina; Angelo Nicosia; Giuseppe Antonio Baratta; Maria Elisabetta Palumbo; Carlotta Scirè; Placido Giuseppe Mineo (Nanomaterials, 2022)
Space exploration missions are currently becoming more frequent, due to the ambition for space colonization in sight of strengthening terrestrial technologies and extracting new raw materials and/or resources. In this field, the study of the materials’ behaviour when exposed to space conditions is fundamental for enabling the use of currently existing materials or the development of new materials suitable for application in extra-terrestrial environments. In particular, the versatility of polymers renders them suitable for advanced applications, but the effects of space radiation on these materials are not yet fully understood. Here, to shed light on the effects of simulated solar wind on a polymeric material, polymethyl methacrylate (PMMA) was produced through radical bulk polymerization. The PMMA in the form of a thin film was subjected to proton beam bombardment at different fluences and in a high vacuum environment, with structural changes monitored through real-time FT-IR analysis. The structure of the residual material was investigated through MALDI-TOF mass spectrometry and 1H-NMR spectroscopy. The collected data allowed us to hypothesize the structural modifications of the PMMA and the related mechanisms.